Spatial transformation of the economy in the post-communist period: The case of the Vilnius urban region - Ubarevičienė, Rūta; Burneika, Donatas (IGiPZ PAN, 2015)
Economic transformation has been gaining ground in the former socialist countries of Central and Eastern Europe since the change of system. This descriptive paper explores the locational patterns of enterprise in the Vilnius urban region during the post-communist transition of Lithuania. Cartographical techniques are used to map the changes that took place between 1994 and 2011. The results show a sharp increase in the number of enterprises in the urban core and a very modest increase outside this zone. However, the maps reveal divergent locational patterns for different sectors of the urban economy
24 cm
Keywords: post-socialist economic development; spatial transformation; Vilnius urban region; Lithuania